Respuesta :

Answer:

Option d. (6,6)

Step-by-step explanation:

(1) 4x-3y=6

(2) 6x-5y=6

Using the equal values method. Let's isolate "x" from each equation:

(1) 4x-3y=6

Adding 3y to both sides of the equation:

4x-3y+3y=6+3y

4x=6+3y

Dividing both sides of the equation by 4:

[tex]\frac{4x}{4}=\frac{6+3y}{4}\\ x=\frac{6+3y}{4}[/tex]

Isolating "x" from the second equation:

(2) 6x-5y=6

Adding 5y to both sides of the equation:

6x-5y+5y=6+5y

6x=6+5y

Dividing both sides of the equation by 6:

[tex]\frac{6x}{6}=\frac{6+5y}{6}\\ x=\frac{6+5y}{6}[/tex]

Equaling y:

y=y

[tex]\frac{6+3y}{4}=\frac{6+5y}{6}[/tex]

Solving for "y": Cross multiplication:

6(6+3y)=4(6+5y)

Applying the distributive property:

6(6)+6(3y)=4(6)+4(5y)

36+18y=24+20y

Subtracting from both sides 18y and 24:

36+18y-18y-24=24+20y-18y-24

12=2y

Dividing both sides by 2:

12/2=2y/2

6=y

y=6

Replacing y by 6 in the any of the equations where we isolated "x":

[tex]x=\frac{6+3y}{4}\\ x=\frac{6+3(6)}{4}\\ x=\frac{6+18}{4}\\ x=\frac{24}{4}\\ x=6[/tex]


The solution is (x,y)=(6,6)

Answer:

Option (d) is correct.

(6, 6) is the solution of the given system of equation.

Step-by-step explanation:

Consider the given equations

4x-3y=6   ....(1)

6x-5y=6    .........(2)

Solving system of equation using elimination method,

Multiply equation (1) by 5 , we get

(1) ⇒ 20x - 15y = 30   ......(3)

Multiply equation (2) by 3 , we get,

(2) ⇒ 18x - 15y = 18  .......(4)

Subtract equation (3) from (4) , we get,

18x - 15y -( 20x - 15y) = 18 - 30

18x - 15y - 20x +15y = -12

18x - 20x = -12

-2x = -12

⇒ x = 6

Also put x = 6 in (1) , we get

(1) ⇒ 4x - 3y = 6

⇒ 4(6) - 3y = 6

⇒ 24 - 3y = 6

⇒  - 3y = 6-24

⇒ - 3y = - 18

⇒ y = 6

Thus, Option (d) is correct.

(6, 6) is the solution of the given system of equation.